TPM1 Gene Trend Among Concentric Hypertrophic Cardiomyopathy Patients in Tertiary Care Hospitals (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: TPM1 (Alpha Tropomyosin Protein) gene mutations were investigated in concentric HCM (Hypertrophic Cardiomyopathy) patients from tertiary hospitals, focusing on exons 5, 7, and 8—regions harboring a third of known pathogenic variants. HCM is an autosomal dominant disorder with diverse presentations, associated with mutations in genes like MYH7, MyBPC3, TNNT2 and TPM1. Located on chromosome 15q22.2, TPM1 encodes a crucial contractile protein in myocytes; its mutations may disrupt actintropomyosin  interaction, leading to atypical hypertrophy  patterns. The study aimed to identify such mutations in concentric HCM patients within our population.Material and methods: In this cross-sectional study, ten  adult patients diagnosed with concentric HCM (90% male, 10% female, average age 44) were included. Genomic DNA was isolated from peripheral blood samples, and the targeted region of the TPM1 gene (2078 bp fragment encompassing exons 5, 7 and 8) was amplified using PCR and sequenced by Sanger sequencing.Results: Data analysis using Geneious® R11 and BLAST tool by NCBI revealed no pathogenic variants in the TPM1 gene within the studied region in any of the ten patients.Conclusion: The absence of mutations in this study may be due to the small targeted region, focus on exonic variants, or low prevalence of TPM1 mutations in the Bangladeshi population. As TPM1 mutations account for only 5% of HCM cases globally, further research using whole-genome sequencing (NGS) is recommended to address these limitations.JCMCTA 2025 ; 36 (2) : 131-136